International Opportunities in Higher Education Promoted by the COVID-19 Pandemic: Results of A Three-Country Teaching-Learning Experience - Jens Holst; Julie Hard; Mathieu JP Poirier (Universitas Pendidikan Ganesha, 2022)
The COVID-19 pandemic has brought challenges and opportunities to teaching in higher education. The sudden pivot from in-person to online education posed unprecedented challenges to both teachers and students. At the same time, the sudden worldwide suspension of traditional ways of lecturing opened a space for experiments with innovative pedagogic approaches and techniques, including various forms of real-time inter-university exchange and student cooperation. COVID-19 pandemic caused a sudden and disruptive shift to emergency remote learning and teaching, as well as a simultaneous halt to international mobility of students, faculty and staff. These changes to established modes of teaching and learning in higher education along with the de facto end of all international mobility efforts led global health course directors from York University in Canada and Fulda University of Applied Sciences in Germany to establish a globally networked learning environment involving shared virtual lectures and international collaborative group projects. Students reported benefits of an enriched learning experience through the sharing of different perspectives, approaches and debates with international professors and peers. Coordination relating to time differences and expectations played a key role in success and overcoming challenges for collaboration among students. The COVID-19 pandemic has shown that cross-border inter-university teaching and learning is a feasible and beneficial pedagogic option.